PENERAPAN MODEL PEMBELAJARAN TPS TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMPN 28 PADANG - Natasya, Arifah (Departemen Matematika, 2023)
Learners need math communication skills. Students of SMP Negeri 28 Padang class VIII lack mathematical communication abilities. Think Pair Share was selected for learning. This research examined whether SMP Negeri 28 Padang grade VIII students who used the Think Pair Share model had stronger mathematics communication abilities than those who used the standard approach. As a fake experiment, this study employs Static Group Design. Simple Random Sampling was utilised. Class VIII.8 was the experimental class and VIII.7 the control class from the draw. The research tool assesses mathematical communication. The data analysis P-value was 0.001. Since P-value < α = 0.05, H0 is rejected. Compare to the standard model, Think Pair Share students have better mathematical communication abilities.Keywords– Think Pair Share, Mathematical Communication Skills, Conventional Learning